Banalitas Empowerment Program, Perlukah Rekonstruksi Pemberdayaan Ekonomi Perempuan? - Saputri, Apik Anitasari Intan; Triana, Nita; Liddini, Laily (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2024)
The purpose of this writing is to explore and reveal government empowerment programs that are not on target. This paper is a non-doctrinal research with qualitative analysis.Gender inequality limits the role of women to access various resources. These limitations make women more vulnerable to poverty. Women's participation as a driver of the family economy is important to get support from the government. In accordance with the mandate of Permendagri Number 1 of 2013 concerning Community Empowerment through the Family Empowerment and Welfare Movement. The result of this study is that the Empowerment and Poverty Alleviation Program in the former Banyumas Resident area has been carried out, but the absorption of funds in the program is still not optimal. This paper is a non-doctrinal research with qualitative analysis. The result of this study is that the Empowerment and Poverty Alleviation Program in the former Banyumas Resident area has been carried out, but the absorption of funds in the program is still not optimal. One of the main factors is the lack of knowledge of the local apparatus in preparing the budget draft, lack of digging Asset Based Communities from the village so that women's empowerment programs experience banality, the target funds that should be used optimally are very slow, not on target. The findings of this study, with the empowerment of women through a productive economy through groups in villages more benefits for families, members can obtain and meet their living needs quickly with the management of funds in their community groups such as KUB (joint business group) Berkah Jaya and also the Inyong Garbage Bank, The government needs to reactualize the empowerment program to the community not only through the top down system but what is needed is bottom up so that the needs of local wisdom from each group in the village can be achieved properly. Keyword:Empowerment, Women, Economy, Family